TURN-TAKING IN "THE LAND OF FIVE TOWERS" NOVEL: IMPLICATIONS FOR THE TEACHING OF PRAGMATICS - Anis Fauziah Handoko; Nur Afifi (Journal of English Language Learning, 2022)
The discouraging level of students’ literacy in Indonesia has encouraged teachers to look for alternatives in teaching, leading to the use of various teaching media to help increase students’ literacy. This study explores the use of novels, a genre of authentic text with interesting and inspirational contents, to help students understand pragmatics and thorough description of the turn-takings and their components in the novels. The method used is turn-taking analysis with two data taken, namely conversations for turn-taking features and narration by the author as turn constructional units. From the data collected, this research uses the conversation analysis method that was initiated by Sack, Schegolff, and Jefferson. The turn-taking feature found in this study is turn-taking in groups of students or when they listen to lectures from the teacher. The narrative section from the writer was used to show how the gaps, overlapping, intonation, or actions of the characters are. This part gave a big limitation to explore because it depends on what the writer wrote in narration. The genre of this novel also will influence what the researcher will find and English students will learn in pragmatics.